Construction, Features and Regulatory Aspects of Organ-chip for Drug Delivery Applications: Advances and Prospective - Gupta, Babita; Malviya, Rishabha; Srivastava, Saurabh; Ahmad, Irfan; Rab, Safia O.; Uniyal, Prerna (Current Pharmaceutical Design, 2024)
Organ-on-chip is an innovative technique that emerged from tissue engineering and microfluidic technologies. Organ-on-chip devices (OoCs) are anticipated to provide efficient explanations for dealing with challenges in pharmaceutical advancement and individualized illness therapies. Organ-on-chip is an advanced method that can replicate human organs' physiological conditions and functions on a small chip. It possesses the capacity to greatly transform the drug development process by enabling the simulation of diseases and the testing of drugs. Effective integration of this advanced technical platform with common pharmaceutical and medical contexts is still a challenge. Microfluidic technology, a micro-level technique, has become a potent tool for biomedical engineering research. As a result, it has revolutionized disciplines, including physiological material interpreting, compound detection, cell-based assay, tissue engineering, biological diagnostics, and pharmaceutical identification. This article aims to offer an overview of newly developed organ-on-a-chip systems. It includes single-organ platforms, emphasizing the most researched organs, including the heart, liver, blood arteries, and lungs. Subsequently, it provides a concise overview of tumor-on-a-chip systems and emphasizes their use in evaluating anti-cancer medications.
Keywords: drug delivery